PRIVACIDAD Y PROTECCIÓN DE DATOS: UN ANÁLISIS DE LEGISLACIÓN COMPARADA - Chen Mok, Susan (2010)
The work presents an analysis of the privacy and protection of information from the perspective of the electronic commerce. One presents the beginning and the protection guarantees of information that must prevail and his application and interpretation in an environment of electronic commerce. There is realized a comparative analysis of the constitutional procedure, laws and projects related to the subject matter of privacy and protection of information of six Latin-American countries: Chile, Colombia, Costa Rica, Ecuador, Mexico and Peru. One presents the jurisprudence applied by the Constitutional Costa Rican Room in this matter. And finally there fulfils an analysis of the Project of Law 15178 Protection law of the Person Opposite to The Treatment of his Personal Information of Costa Rica presenting his successes, emptinesses.